DANCE CURRICULUM MODEL FOR HIGH SCHOOLS IN PALACES STUDENTS IN ROMANIA (GYMNASIUM, 2017)
The research undertaken was intended to achieve a high school dance curriculum educational Palaces pupils for contribute to the knowledge, skills and abilities to the all practitioners participating in these programs. The research was conducted on subjects selected from three centres of our country, namely: Braşov, Sălaj, Vaslui, where were implemented the data proposed by the curricula. Based on the data collection after assessment tests resulted significant figures confirming the proposals. Also, were made the conclusions and suggestions.